Can biomarkers improve the rational use of antibiotics?. Issue 4 (August 2018) - Fontela, Patricia S.; O'Donnell, Shauna; Papenburg, Jesse
Abstract : Purpose of review: We aim to review recent literature about the use of biomarkers to guide the initiation and duration of antibiotic treatments for suspected bacterial infections. Recent findings: Several good quality meta-analyses show that procalcitonin can be safely used to guide antibiotic-related decisions, especially for respiratory infections, thereby decreasing unnecessary antibiotic exposure. Furthermore, the use of CRP-based algorithms to guide antibiotic initiation in primary care patients with acute respiratory infections is associated with a reduction in antibiotic use without an increase in adverse events. Regarding neutrophil CD64 and serum amyloid A, more good-quality evidence is needed to assess their utility as biomarkers to tailor antibiotic use. Finally, transcriptomics, metabolomics and proteomics are promising tools for the development of tests to differentiate specific host responses to viral, bacterial and noninfectious stimuli, but such tests still need further validation. Summary: Evidence shows that the use of biomarkers, procalcitonin and CRP, can safely reduce unnecessary antibiotic prescriptions in certain infectious syndromes. The clinical utility of host-based strategies such as transcriptomics, metabolomics and proteomics for the diagnosis of infectious diseases has yet to be evaluated, as well as considerations such as costs, technical complexity and result turnaround time.